The isomerization of △⁵–androstene-3,17-dione by hGST A3-3: the pursuit of catalytic perfection in proton abstraction reactions of 3-ketosteroids - Daka, Jonathan Lembelani (My University, 2015)
The seemingly simple proton abstraction reactions underpin many chemical transformations including isomerization reactions and are thus of immense biological significance. Despite the energetic cost, enzyme-catalyzed proton abstraction reactions show remarkable rate enhancements. The pathways leading to these accelerated rates are numerous and on occasion partly enigmatic. The isomerization of the steroid, Δ5- androstene-3,17-dione by the human glutathione transferase A3-3 in mammals was investigated to gain insight into the mechanism. Particular emphasis was placed on the nature of the transition state, the intermediate suspected of aiding this process and the hydrogen bonds postulated to be the stabilizing forces of these transient species. Kinetics studies on Δ5-androstene-17-one, a substrate that is incapable of forming hydrogen bonds reveal that such stabilizing forces are not a requirement to explain the observed rate enhancements. The UV-Vis detection of the intermediate places this specie in the catalytic pathway while fluorescence spectroscopy is used to obtain the binding constant of the intermediate analogue equilenin. Analysis of the kinetics data in terms of the Marcus formalism indicates that the human glutathione transferase A3-3 lowers the intrinsic kinetic barrier by 3 kcal/mole. The results lead to the conclusion that this reaction proceeds through an enforced concerted mechanism in which the barrier to product formation is kinetically insignificant.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2014.
Keywords: Protons.; Isomerization.; Androstenedione.; Glutathion transferase.